2014
DOI: 10.1002/acr.22223
|View full text |Cite
|
Sign up to set email alerts
|

Knee Power Is an Important Parameter in Understanding Medial Knee Joint Load in Knee Osteoarthritis

Abstract: ObjectiveTo determine the extent to which knee extensor strength and power explain variance in knee adduction moment (KAM) peak and impulse in clinical knee osteoarthritis (OA).MethodsFifty-three adults (mean ± SD age 61.6 ± 6.3 years, 11 men) with clinical knee OA participated. The KAM waveform was calculated from motion and force data and ensemble averaged from 5 walking trials. The KAM peak was normalized to body mass (Nm/kg). The mean KAM impulse reflected the mean total medial knee load during stride (Nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
10
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 48 publications
2
10
1
1
Order By: Relevance
“…That study also showed that knee adduction moment was not related to knee extensor strength, but was related to knee extensor power. [ 27 ]Although no correlation was observed between knee extensor strength and adduction moment in the present study, a close correlation was found between quadriceps endurance and knee adduction moment. Direct comparison of the results of the two earlier studies mentioned above with those of the present work is made difficult by the different measurement variables, such as isokinetic strength, power, and endurance, used in the studies.…”
Section: Discussioncontrasting
confidence: 64%
See 2 more Smart Citations
“…That study also showed that knee adduction moment was not related to knee extensor strength, but was related to knee extensor power. [ 27 ]Although no correlation was observed between knee extensor strength and adduction moment in the present study, a close correlation was found between quadriceps endurance and knee adduction moment. Direct comparison of the results of the two earlier studies mentioned above with those of the present work is made difficult by the different measurement variables, such as isokinetic strength, power, and endurance, used in the studies.…”
Section: Discussioncontrasting
confidence: 64%
“…Agreeing with our results, recent studies also found no correlation between knee extensor strength and knee adductor moment. [ 27 , 28 ]A previous study assessed the relationship between quadriceps strength and knee adduction moment in patients with osteoarthritis. That study, which measured quadriceps strength and peak knee adduction moment during walking in 184 subjects with medial knee osteoarthritis, found no significant association between quadriceps strength and peak knee adduction moment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, in 40 participants with established knee OA, knee extension muscle power, measured isotonically using a dynamometer at low external resistances, was more predictive of WOMAC-assessed function than peak isometric muscle strength (17). Isotonic knee extensor muscle power was also superior to muscle strength in determining medial knee loading and adduction moments during kinematic gait trials in 53 patients with clinical knee OA (18). In the current study, we incorporated a dynamic, well-validated assessment of leg extensor muscle power within a large population of subjects with knee OA, and demonstrated the novel clinical importance of muscle power as an independent predictor of pain and quality of life in these symptomatic patients.…”
mentioning
confidence: 93%
“…(12, 15, 16) Two small studies in knee OA patients have demonstrated that lower extremity power is more predictive of self-reported function than strength,(17) and muscle power is superior than strength in determining medial knee loading and adduction moments. (18) However, no study to date has comprehensively investigated lower extremity muscle power as a potential determinant of disease severity in knee OA or evaluated specific relationships between muscle power, knee pain and quality of life among individuals with symptomatic knee OA.…”
mentioning
confidence: 99%